Satisfacción laboral del personal de enfermería del hospital provincial generaldocente riobamba y su relación con el desempeño profesional durante el periodo enero a junio del 2010” - Martínez, Miriam (2010)
Nurses' work demands an array of activities that need to be exposed to multiple attacks that result in the physical and emotional development of professional satisfaction of nurses is an essential factor in maintaining balance in their activity. Inthe country there have been no studies on job satisfaction of nurses and itsrelationship to professional performance, that is why we conducted a prospectivedescriptive intervention study and cross sectional PROVINCIAL GENERAL HOSPITAL TEACHING RIOBAMBA during the month of January and June 2010. The universe was the whole active nursing staff at the time the study.